Pengaruh Keterampilan Komunikasi Matematis terhadap Pemahaman Konsep Matematika Siswa Kelas VI di Sekolah LH - Patricia Daniela Iman; Samuel Lukas (Departement of Mathematics Education, 2024)
Mathematics is one of the important sciences to be taught to children from an early age. Concepts in mathematics can shape students' knowledge so as to help in the development of knowledge at a higher level of education. The purpose of this study was to determine the influence of mathematical communication skills on the understanding of concepts possessed by grade VI elementary school students in LH schools. This study was conducted using a quantitative approach by distributing five test items to 54 students. The results found that mathematical communication skills positively affect on understanding of concepts. Moreover, indicator of using mathematical language correctly in expressing mathematical ideas is the most influential than that of the other three indicators on students' mathematical communication skills on understanding concepts.